Giant cell aortitis leading to Stanford type B and type A aortic dissection. (October 2017) - El-Medany, Ahmed; Wallace, W; Mcrorie, E; Tan, Sy; Lim, K
Lesson: This report provides a rare histological example and the appropriate management of spontaneous aortic dissection secondary to giant cell arteritis.